(untitled) (Bangladesh Journal of Botany, 2021)
The energy exchange ratio of cultivation and different parameter values of input affecting the organic production of kiwifruit in the mid-hill Himalayan region of India during 2017 and 2018 was determined. The experimental trial was divided into 7 organic treatment i.e. T1 to T3 was sole application on equivalence 100 per cent Dairy manure (DM), Vermicompost (VC) and Poultry manure, T4 to T7 was a compound application of 50: 50 DM: PM, DM: VC and VC: PM and T7 in which DM = PM = VC applied on N equivalence. Five foliar sprays of organic formulation were applied in each of the treatment. The Energy efficiency and econometric analysis of organic kiwifruit production were examined. The highest energy inputs unit per hectare was utilized by T1 out of which over 86 per cent were from organic manure inputs and provided 26401.02 MJ/ha. The highest yield per hectare, as well as the output energy were observed in the treatment T5. Whereas the highest energy ratio, energy productivity, and specific energy were recorded under T2. Likewise, the highest productivity ratio and benefit-cost ratio were recorded under T7 which was followed by T2. From a farming point of view, the T2 gave the superior result because it has provided optimum amount output along with maximum returns. Bangladesh J. Bot. 50(4): 1051-1057, 2021 (December)